Essence of Moral Education: Luqman Speaks, the Students Remain Silent? - Syamsuddin, Syamsuddin (Education and Talent Development Center Indonesia (ETDC Indonesia), 2025)
One-way communication between an active teacher/ustaz and passive students can sometimes hinder moral teaching. This study raises important considerations about the effectiveness of internalizing moral ideals, especially for academics who are also students. Is the